The association between arterial stiffness and cancer occurrence: Data from Kailuan cohort study - Jiang, Yinong; Xing, Aijun; Hidru, Tesfaldet Habtemariam; Li, Jiatian; Yang, Xiaolei; Chen, Shuohua; Xia, Yun-Long; Wu, Shouling (Frontiers in Cardiovascular Medicine, 2023)
Background This study aimed to investigate whether increased arterial stiffness, measured by brachial-ankle pulse wave velocity (baPWV) is associated with cancer. Materials and methods A total of 45,627 Chinese adults underwent a baPWV examination. The participants were followed up from 1st January 2012 to 31st December 2018. Cox proportional hazards model was used to assess the association between the baPWV values and cancer. Results During a total follow-up duration of 172,775.69 person-years, there were 553 new cases of cancer. The subjects in the highest baPWV group showed an increased risk of cancer when compared with the lowest baPWV group as confirmed by multivariate-adjusted hazard ratios (HR = 1.51, 95% CI = 1.14∼2.00) in the entire cohort. Compared with participants in the lowest baPWV group, the HRs (95% CI) for digestive cancer in the second and third groups were 1.55 (1.00∼2.40) and 1.99 (1.19∼3.33), respectively. The Kaplan-Meier analysis demonstrated a significant increase in cancer in participants with a baPWV ≥ 18 m/s (P < 0.001). Compared with the lowest baPWV group, the highest baPWV group showed an increased risk of cancer in men (HR = 1.72, 95% CI = 1.22∼2.43) and those < 60 years (HR = 1.75, 95% CI = 1.20∼2.55), respectively. Conclusion Increased arterial stiffness measured by baPWV is associated with cancer occurrence, especially digestive cancer occurrence. Clinical trial registration ClinicalTrials.gov, identifier ChiCTR-TNRC-11001489.